A study on calf circumference at birth as a screening indicator to predict low birth weight babies in and around rural area - S V Madanika,; Pavan Kumar D,; P Sreekavya, (Indian Journal of Child Health, 2021)
Background: Birth weight is a significant indicator for healthy survival and overall growth and development of the child. Appropriate timely care of low birth weight (LBW) newborns is important but it is difficult in developing countries since many are home deliveries with inadequate facilities to weigh the newborn. Objective: The present study is an attempt to utilize calf circumference (CC) as a screening indicator to predict LBW babies at birth. Materials and Methods: A hospital-based prospective cross-sectional study was conducted in a tertiary care hospital Mandya, Karnataka for a period of 3 months between September 2020 and December 2020 comprising total of 100 neonates delivered during this study period. Birth weight was recorded using a digital weighing scale within 24 h of the delivery. CC was measured according to the standard guidelines. Statistical analysis was performed using the SPSS statistical software. Results: The majority of mothers were in the age group of 20–24 years. Among 100 newborns, 21.00% were LBW babies. The mean CC of LBW babies was 9.53±1.10 cm, whereas for the normal weight babies, it was 10.80±1.05 cm. Pearson’s correlation coefficient between CC and birth weight was statistically significant (p